Skip to main content

On the convergence of x n =f( x n 2 , x n 1 ) when f(x,y)<x

Abstract

Given the second-order difference equation x n =f( x n 2 , x n 1 ), if fC[ ( 0 , ) 2 ,(0,)] and f(x,y)<x, then ( x 2 n , x 2 n + 1 ) tends either to (L,0) or to (0,L) for some L0. In this paper we show that if f(x,y) decreases in y, then for any x 0 there is an x 1 such that x n monotonically decreases to 0. We also prove that if xyf(x,y)f(y,f(x,y)), then for any L0 and x 0 >L there is an x 1 such that ( x 2 n , x 2 n + 1 )(L,0) and similarly, for any x 0 there is an x 1 such that ( x 2 n , x 2 n + 1 )(0,L). The class of functions satisfying the latter condition includes any function of the form f(x,y)= x 1 + h ( x , y ) y , where h is symmetric and increases in y.

MSC:39A11, 39A23.

1 Introduction

Let be the set of functions fC[ ( 0 , ) 2 ,(0,)] satisfying the condition

  1. (A)

    f(x,y)<x.

In this paper, we investigate the convergence of the solutions of the second-order difference equation

x n =f( x n 2 , x n 1 ),n=2,3,
(1)

for the following two subsets of :

F 1 = { f F : f ( x , y )  decreases in  y } , F 2 = { f F : x y f ( x , y ) f ( y , f ( x , y ) ) } .

We note that by ‘decreasing’ and ‘increasing’ we mean non-increasing and non-decreasing, respectively.

Continuity and (A) imply that if fF, then ( x 2 n , x 2 n + 1 ) tends either to (L,0) or to (0,L) for some L0. The convergence of the positive solutions of equation (1) has been investigated before for functions whose restriction to ( 0 , ) 2 is in and which are strictly monotonic in both of their variables, typically assuming that

  1. (a)

    f C [ [ 0 , ) 2 ,[0,)] and its restriction f ¯ to ( 0 , ) 2 is in ,

  2. (b)

    f(x,0)=x,

  3. (c)

    f ¯ strictly increases in x and strictly decreases in y.

Let f be of this type. Then, since f ¯ F, every positive solution tends either to (L,0,L,0,) or to (0,L,0,L,) for some L0, the only periodic solutions of equation (1), with (0,0,0,0,) being the unique equilibrium solution (see, e.g. [1]). The question of the existence of positive solutions converging to the equilibrium solution in the special case f(x,y)= x 1 + α y (x,y0) was raised by Kulenovic and Ladas in [2]. Kent gave an affirmative answer in [1] by showing that, in general, if f satisfies (a), (b), (c) and the condition that

  1. (d)

    f is differentiable and there is a differentiable function g such that x n 2 =g( x n 1 , x n ), with some further properties detailed in [1],

then for any x 0 >0 there is an x 1 >0 such that x n monotonically decreases to 0. We note that Janssen and Tjaden [3] had previously proved this for f(x,y)= x 1 + y and x 0 =1. As we shall see, Kent’s conclusion follows from much weaker assumptions, namely that (a) holds and f ¯ (x,y) decreases in y.

To be more precise, we show (cf. Theorem 2.1) that if f F 1 , then for any x 0 there is an x 1 such that x n monotonically decreases to 0. Also, for any x 1 , if x 1 f(x, x 1 ) for some x, then there is an x 0 such that x n monotonically decreases to 0. Theorem 2.1 also applies to f(x,y)=x α y + β x A y + β x , investigated by Chan et al. in [4]. In their paper, they prove, inter alia, that if 0<α<A and 0<β, then there are positive initial values for which x n in equation (1) monotonically decreases to 0. Since the restriction of f to ( 0 , ) 2 is in F 1 , their result also follows from Theorem 2.1 in a stronger form.

For functions in F 2 we show (cf. Theorem 2.2) that if L0, then for any x 0 >L there is an x 1 such that ( x 2 n , x 2 n + 1 )(L,0) and for any x 1 , if x 1 +Lf(x, x 1 ) for some x, then there is an x 0 such that ( x 2 n , x 2 n + 1 )(L,0). Similar results hold for convergence to (0,L).

The class F 2 includes several types of functions of interest. For instance, as we shall see later on, F 2 F 1 contains any function of the form f(x,y)= x 1 + h ( x , y ) y , where hC[ ( 0 , ) 2 ,(0,)] is symmetric, i.e. h(x,y)=h(y,x), and increases in y. In particular, F 2 F 1 includes f(x,y)= x 1 + α y for any α>0. Actually, functions of this form, defined on [ 0 , ) 2 , belong to another subset of the set of functions satisfying (a), (b) and (c) above, for which a result similar to, but stronger than Theorem 2.2 was proved in [5]. Given any function in this set, for any L0, the set of positive initial values ( x 0 , x 1 ) for which ( x 2 n , x 2 n + 1 )(L,0) is a surjective, strictly increasing (and hence continuous) function from (L,) to (0,).

2 Main results

In order to prove our main results, we shall think of the difference equation (1) as a recursively defined sequence of functions of the initial conditions, namely

f 0 ( x , y ) = x , f 1 ( x , y ) = y , f n ( x , y ) = f ( f n 2 ( x , y ) , f n 1 ( x , y ) ) for  n 2 .

Putting r n = f 2 n , s n = f 2 n + 1 , we have r 0 (x,y)=x, s 0 (x,y)=y and, for n1,

r n ( x , y ) = f ( r n 1 ( x , y ) , s n 1 ( x , y ) ) , s n ( x , y ) = f ( s n 1 ( x , y ) , r n ( x , y ) ) .

Let fF. Then the recursive relationships above imply that r n , s n C[ ( 0 , ) 2 ,(0,)] for any n, and by (A)

x = r 0 ( x , y ) > r 1 ( x , y ) > r 2 ( x , y ) > , y = s 0 ( x , y ) > s 1 ( x , y ) > s 2 ( x , y ) > .

In particular, for n1, r n satisfies (A), hence r n F, and s n satisfies the condition

(A) f(x,y)<y.

We shall write R and S for the pointwise limits of r n and s n , respectively. R and S map ( 0 , ) 2 to [0,) and, since r n (x,y)>R(x,y), s n (x,y)>S(x,y), R and S satisfy (A) and (A), respectively. However, as we shall see in Example 3.4, R and S are not necessarily continuous. If L=R(x,y) and M=S(x,y) were both positive, then, by the recursive relationship between r n and s n and the continuity of f, L=f(L,M), contradicting (A). Therefore, either R(x,y)=0 or S(x,y)=0, i.e. R(x,y)S(x,y)=0 for any x and y. We also observe that R and S have the same range, since R(x,y)=S(y,f(x,y)) and S(x,y)=R(y,f(x,y)). In particular, 0 is in the range of both functions.

Our main results will characterise, in terms of the functions R and S, the sets of initial conditions under which ( x 2 n , x 2 n + 1 ) in equation (1) tends to (L,0) or to (0,L). For any L0, let us put R L and S L , respectively, for these sets, so that

R L = { ( x , y ) : R ( x , y ) = L  and  S ( x , y ) = 0 } , S L = { ( x , y ) : R ( x , y ) = 0  and  S ( x , y ) = L } .

We note that for L>0, since R(x,y)SS(x,y)=0, R L and S L are simply the L-level sets of R and S, respectively. Also, R 0 is the intersection of the 0-level sets of R and S and R 0 = S 0 .

Regarding R L and S L as relations, the theorems below characterise their domain and their range, Theorem 2.1 for L=0 and any f F 1 and Theorem 2.2 for any L0 and any f F 2 .

Theorem 2.1 Let f F 1 . Then

  1. (i)

    for any a there is a b in the interval [f(a,a),a] for which R(a,b)=S(a,b)=0,

  2. (ii)

    for any b, if there is a b such that bf( b ,b), then there is an a in the interval [b, b ] for which R(a,b)=S(a,b)=0.

Theorem 2.2 Let f F 2 and L0. Then

  1. (i)

    for any a>L there is a b in the interval [f(aL,a),aL] for which R(a,b)=L, S(a,b)=0,

  2. (ii)

    for any b, if there is a b such that b+Lf( b ,b), then there is an a in the interval [b+L, b ] for which R(a,b)=L, S(a,b)=0,

  3. (iii)

    for any a there is a b in the interval [f(a+L,a),a+L] for which R(a,b)=0, S(a,b)=L,

  4. (iv)

    for any b>L, if there is a b such that bLf( b ,b), then there is an a in the interval [bL, b ] for which R(a,b)=0, S(a,b)=L.

Remark 2.1 If lim x f(x,b)=, then of course there is a b satisfying the condition in (ii) of Theorem 2.1 and in (ii), (iv) of Theorem 2.2. The condition is not necessary, as shown later on by Example 3.1.

The proofs of Theorem 2.1 and Theorem 2.2 will follow immediately from the two lemmas below. In order to motivate these lemmas, we observe that given fF and L0, a sufficient condition for R(a,b)=L, S(a,b)=0 is that for all n

r n (a,b)L s n (a,b) r n + 1 (a,b)L,

i.e. r n (a,b) s n (a,b)L0 and s n (a,b) r n + 1 (a,b)+L0. This is sufficient, since either R(a,b)=0 or S(a,b)=0. Similarly, a sufficient condition for R(a,b)=0, S(a,b)=L is that for all n

r n (a,b) s n (a,b)L r n + 1 (a,b),

i.e. r n (a,b) s n (a,b)+L0 and s n (a,b) r n + 1 (a,b)L0. In particular, if L=0, then r n (a,b) s n (a,b) r n + 1 (a,b) and so R(a,b)=S(a,b)=0. We also observe that if f F 2 , then the first condition is also necessary for R(a,b)=L, S(a,b)=0 and the second one is also necessary for R(a,b)=0, S(a,b)=L. This is because if f F 2 , then for any x, y and n, r n (x,y) s n (x,y) r n + 1 (x,y) s n + 1 (x,y) and s n (x,y) r n + 1 (x,y) s n + 1 (x,y) r n + 2 (x,y).

According to the discussion above, in order to prove that given a there is a b such that R(a,b)=L and S(a,b)=0, it is sufficient to show that there is a b for which the functions p n (y)= r n (a,y) s n (a,y)L and q n (y)= s n (a,y) r n + 1 (a,y)+L are both non-negative for all n. Similarly, given a and p n (y)= r n (a,y) s n (a,y)+L, q n (y)= s n (a,y) r n + 1 (a,y)L, if both functions are non-negative for all n, then R(a,b)=0 and S(a,b)=L.

Lemma 2.1 below provides sufficient conditions ensuring that, in general, the functions in two sequences of continuous real functions are all non-negative for some argument. Lemma 2.2 uses Lemma 2.1 to show that if L0 and fF has the property that f(x,y)f(y,f(x,y))±L whenever xy=±L, then statements (i), (ii), (iii) and (iv) in Theorem 2.2 are true for L and f. Since any function in F 1 has this property for L=0, Theorem 2.1 follows from Lemma 2.1, and since any function in F 2 has this property for any L0, so does Theorem 2.2.

Lemma 2.1 Let p n , q n C[[a,b],(,)], n=0,1, , and put

S a b = { x : p n ( x ) 0  and  q n ( x ) 0  for all  n } .
  1. (i)

    If

    1. (a)

      for all n and x, either p n (x)>0 or q n (x)>0,

    2. (b)

      for all n and x, if p n (x)=0 then p n + 1 (x)0 and if q n (x)=0 then q n + 1 (x)0,

    3. (c)

      p 0 (b)0 and q 0 (a)0,

    then S a b .

  2. (ii)

    If (a) holds and (b), (c) are replaced by

(b′) for all n and x, p n (x) p n + 1 (x) and q n (x) q n + 1 (x),

(c′) p N (b)0 and q M (a)0 for some N,M0,

then S a b .

Proof (i) Let p,qC[[a,b],(,)] be any two functions such that for any x either p(x)>0 or q(x)>0 and p(b)0, q(a)0. Then q(a)0 implies that p(a)>0 and so, since p(b)0, p has a smallest root b in (a,b]. Therefore, p>0 on [a, b ) and p( b )=0. But then q( b )>0 and so, since q(a)0, q has a greatest root a in [a, b ). Hence, q>0 on ( a , b ] and q( a )=0. Thus, there is an interval [ a , b ][a,b] such that p>0 on [ a , b ) and q>0 on ( a , b ] and p( b )=q( a )=0.

Let us now assume that the hypothesis of (i) holds. Then, by the above, there is an interval [ a 0 , b 0 ][a,b] such that p 0 >0 on [ a 0 , b 0 ) and q 0 >0 on ( a 0 , b 0 ] and p 0 ( b 0 )= q 0 ( a 0 )=0. Now suppose that there is an interval [ a n , b n ] such that p n >0 on [ a n , b n ), q n >0 on ( a n , b n ] and p n ( b n )= q n ( a n )=0. Then, by (b), p n + 1 ( b n ) p n ( b n )=0 and q n + 1 ( a n ) q n ( a n )=0. Therefore, by the above, there is an interval [ a n + 1 , b n + 1 ][ a n , b n ] such that p n + 1 >0 on [ a n + 1 , b n + 1 ), q n + 1 >0 on ( a n + 1 , b n + 1 ] and p n + 1 ( b n + 1 )= q n + 1 ( a n + 1 )=0. Hence, by induction, there is a descending sequence [ a 0 , b 0 ][ a 1 , b 1 ][ a 2 , b 2 ] of intervals such that p n >0 on [ a n , b n ), q n >0 on ( a n , b n ] and p n ( b n )= q n ( a n )=0.

Finally, let I= n [ a n , b n ]. Then I is a non-empty closed interval and I S a b . We note that if int(I), then p n and q n are both positive on int(I).

  1. (ii)

    If, say, MN, then p N (a)0 by (b′). Therefore, by (i)

    { x : p n ( x ) 0  and  q n ( x ) 0  for  n N }

and by (b′), {x: p n (x)0 and  q n (x)0 for nN}= S a b . □

Remark 2.2 (Approximating an element of S a b )

Suppose that p n , q n satisfy the conditions of Lemma 2.1(ii) on an interval [a,b], so that S a b . Choose a c(a,b), say c=(a+b)/2. Suppose that either p N (c)0 or q N (c)0 for some N0. Then, by Lemma 2.1(ii), p n and q n satisfy the conditions of Lemma 2.1(ii) either on [a,c] if p N (c)0, or on [c,b] if q N (c)0. Therefore, if p N (c)0, then S a c and if q N (c)0, then S c b . Since S a c , S c b S a b , in either case we have a better approximation of an element of S a b . The method will fail if p n (c)>0 and q n (c)>0 for all n0 (in which case c S a b ).

Lemma 2.2 Let fF. Suppose that for an L0 and any x and y,

if xy=±L then f(x,y)f ( y , f ( x , y ) ) ±L.
(2)

Then statements (i), (ii), (iii) and (iv) in Theorem  2.2 are true for f and L.

Proof First we observe that

( r n ( x , y ) s n ( x , y ) ± L ) + ( s n ( x , y ) r n + 1 ( x , y ) L ) = r n ( x , y ) r n + 1 ( x , y ) > 0 .
(3)

Also, it follows from (2) that

if  r n ( x , y ) s n ( x , y ) ± L = 0  then  r n + 1 ( x , y ) s n + 1 ( x , y ) ± L 0 , if  s n ( x , y ) r n + 1 ( x , y ) ± L = 0  then  s n + 1 ( x , y ) r n + 2 ( x , y ) ± L 0 .
(4)

Then:

  1. (i)

    Let a>L. Put p n (y)= r n (a,y) s n (a,y)L and q n (y)= s n (a,y) r n + 1 (a,y)+L. Then p 0 (aL)=a(aL)L=0. By (2), f(aL,a)f(a,f(aL,a))L and so q 0 (f(aL,a))=f(aL,a)f(a,f(aL,a))+L0. Together with (3) and (4) this means that p n and q n satisfy the hypothesis of Lemma 2.1(i) on the interval [f(aL,a),aL]. Therefore, there is a b in the interval [f(aL,a),aL] such that p n (b)0 and q n (b)0 for all n0 and so R(a,b)=L, S(a,b)=0.

  2. (ii)

    Given b, suppose that there is a b such that b+Lf( b ,b). Put p n (x)= s n (x,b) r n + 1 (x,b)+L and q n (x)= r n (x,b) s n (x,b)L. Then p 0 ( b )=bf( b ,b)+L0 and q 0 (b+L)=(b+L)bL=0. Together with (3) and (4) this means that p n and q n satisfy the hypothesis of Lemma 2.1(i) on the interval [b+L, b ]. Therefore, there is an a in the interval [b+L, b ] such that p n (b)0 and q n (b)0 for all n0 and so R(a,b)=L, S(a,b)=0.

  3. (iii)

    Given a, put p n (y)= r n (a,y) s n (a,y)+L and q n (y)= s n (a,y) r n + 1 (a,y)L. Then p 0 (a+L)=a(a+L)+L=0. By (2), f(a+L,a)f(a,f(a+L,a))L and so q 0 (f(a+L,a))=f(a+L,a)f(a,f(a+L,a))L0. Together with (3) and (4) this means that p n and q n satisfy the hypothesis of Lemma 2.1(i) on the interval [f(a+L),a+L]. Therefore, there is a b in the interval [f(a+L,a),a+L] such that p n (b)0 and q n (b)0 for all n0 and so R(a,b)=0, S(a,b)=L.

  4. (iv)

    Let b>L and suppose that there is a b such that bLf( b ,b). Put p n (x)= s n (x,b) r n + 1 (x,b)L and q n (x)= r n (x,b) s n (x,b)+L. Then p 0 ( b )=bf( b ,b)L0 and q 0 (bL)=(bL)b+L=0. Together with (3) and (4) this means that p n and q n satisfy the hypothesis of Lemma 2.1(i) on the interval [bL, b ]. Therefore there is an a in the interval [bL, b ] such that p n (b)0 and q n (b)0 for all n0 and so R(a,b)=0, S(a,b)=L. □

We can now prove Theorem 2.1 and Theorem 2.2.

Proof of Theorem 2.1 and Theorem 2.2 If f F 1 , then f(x,x)f(x,f(x,x))0, since f(x,x)<x. Thus f satisfies the hypothesis of Lemma 2.2 for L=0 and so Theorem 2.1 holds.

If f F 2 then xyf(x,y)f(y,f(x,y)) and so f satisfies the hypothesis of Lemma 2.2 for any L0 and Theorem 2.2 follows. □

Remark 2.3 (Approximating initial conditions for convergence)

Let f F 2 and L0. Given any a>L, define p n and q n as in (i) of the proof of Lemma 2.2 above. Then, using the bisection method described in Remark 2.2, we can (usually) approximate a b such that R(a,b)=L and S(a,b)=0 to any degree of accuracy. Similarly, if we define p n and q n as in (iii) of the proof of Lemma 2.2, then, given any a, we can (usually) approximate a b such that R(a,b)=0 and S(a,b)=L.

3 Applications

In this section, we give a few examples of applying the results of Section 2. We also show that R (and hence S) is not necessarily continuous for functions in . We note that, in general, the elements of can be written as f(x,y)= x 1 + g ( x , y ) , with gC[ ( 0 , ) 2 ,(0,)] and vice versa.

We shall use the following proposition in the examples.

Proposition 3.1

  1. (i)

    Let F 21 be the set of functions of the form

    f(x,y)= x 1 + h ( x , y ) y ,x,y>0,

    where hC[ ( 0 , ) 2 ,(0,)] is symmetric and increases in y (and hence also in x). Then F 21 F 2 F 1 .

  2. (ii)

    Let F 22 be the set of functions of the form

    f(x,y)= x 1 + g ( y ) ,x,y>0,

    where g:(0,)(0,) is differentiable, g(y)0 as y0, yg(y) and g (y) ( 1 + g ( y ) ) 2 . Then F 22 F 2 .

Proof (i) First of all, functions in F 21 (strictly) decrease in y and so they are in F 1 . Next we note that if fF is written as f(x,y)= x 1 + g ( x , y ) , then xf(x,y)=f(x,y)g(x,y). Therefore, if f F 21 , then

x f ( x , y ) = f ( x , y ) h ( x , y ) y = f ( x , y ) h ( y , x ) y > f ( x , y ) h ( y , f ( x , y ) ) f ( y , f ( x , y ) ) = f ( y , f ( x , y ) ) h ( y , f ( x , y ) ) f ( x , y ) = y f ( y , f ( x , y ) ) .

Therefore, F 21 F 2 .

  1. (ii)

    Let us put e(x,y)=(xy)(f(x,y)f(y,f(x,y))). Then, for any y, e(x,y)0 as x0, and so in order to show that e(x,y)0, i.e. that F 22 F 2 , it will be sufficient to demonstrate that for any y, e(x,y) increases in x.

The partial derivative e x can be written as

e x ( x , y ) = 1 ( f x ( x , y ) f y ( y , f ( x , y ) ) f x ( x , y ) ) = 1 f x ( x , y ) ( 1 f y ( y , f ( x , y ) ) ) = 1 1 1 + g ( y ) ( 1 + y g ( f ( x , y ) ) ( 1 + g ( f ( x , y ) ) ) 2 ) .

If g (y) ( 1 + g ( y ) ) 2 and yg(y), then 1+y g ( f ( x , y ) ) ( 1 + g ( f ( x , y ) ) ) 2 1+y1+g(y) and so e x (x,y)0, i.e. e(x,y) increases in x for any y, as claimed. □

Functions in F 21 do not have to be monotonic in x. For instance, f(x,y)= x 1 + x 2 y 3 is not monotonic in x (for any y). Also, functions in F 22 strictly increase in x, but they are not necessarily monotonic in y (cf. Example 3.2). Finally, we note that f(x,y)= x 1 + y is in F 21 F 22 .

Example 3.1 Let f(x,y)= x 1 + x y 2 , x,y>0. We note that if we extend f to [ 0 , ) 2 , then it satisfies (a), (b) and (c) of Section 1.

Since f is in F 21 , Theorem 2.2 holds for f by Proposition 3.1(i). For instance, if L=3 and a=4, then there is a b in the interval [f(43,4),43]=[ 1 17 ,1] such that R(4,b)=3. Using the bisection method described in Remark 2.3, we can get a better approximation for such a b. After seven iterations we find that the interval [0.264706,0.272059] contains a b such that R(4,b)=3.

Similarly, after seven iterations of the bisection method we find that there is a b in the interval [1.01538,1.04615] such that R(4,b)=S(4,b)=0. Given such a b, f(x,b)< 1 b 2 <1<b for any x, showing that the condition in (ii) and (iv) of Lemma 2.2 - and hence in (ii) of Theorem 2.1 and (ii) and (iv) of Theorem 2.2 - is not necessary.

Since R(x,y)< r 1 (x,y)=f(x,y)< 1 y 2 , given any b and L such that L 1 b 2 , there is no a satisfying R(a,b)=L. In fact, there is a B>1 such that if bB then R(x,b)=0 and S(x,b)>0 for any x. In order to show this, let us put h(u,v)=vf(u,v) and let z={(u,v):h(u,v)=0} be the level set of h for 0. As h(u,v) (strictly) decreases in u and strictly increases in v, z is a strictly increasing function. Since h(u,v) strictly increases in v,

if v<z(u) then v<f(u,v).
(5)

For any u(0,), lim v 0 h(u,v)=u<0 and h(u,1)=1 u 1 + u >0. Therefore, 0<z(u)<1, i.e. z maps (0,) to (0,1). Also, for any v(0,1), h( v 1 v 3 ,v)=0 and so z is surjective. Thus z is a strictly increasing surjective function from (0,) to (0,1), hence it is also continuous. Therefore, since lim u 0 z(u)=0 and lim u z(u)=1, z(u)= 1 u 2 has a unique solution B>1, and then

1 u 2 z(u)for any uB.
(6)

Since f(x,b)< 1 b 2 for any x and, by (6), 1 b 2 z(b) for any bB, we see that if bB, then f(x,b)<z(b) for any x. Therefore, by (5), if bB then r 1 (x,b)=f(x,b)<f(b,f(x,b))= s 1 (x,b) for any x. Since f F 2 , this means that if bB then R(x,b)=0 and S(x,b)>0 for any x.

Example 3.2 Let f(x,y)= x 1 + y + 1 2 y sin 2 ( y ) , x,y>0. Put g(y)=y+ 1 2 y sin 2 (y). Then g(y)0 as y0, yg(y) and g (y)=1+ 1 2 sin 2 (y)+ 1 2 ysin(2y)1+y1+g(y) ( 1 + g ( y ) ) 2 . Therefore, f F 22 and so, by Proposition 3.1(ii), Theorem 2.2 holds for f. We observe that g(y) is not monotonic in y (for any x), so neither is f(x,y).

Example 3.3 Let f(x,y)= x 1 + y / x , x,y>0. Since

(xy) ( f ( x , y ) f ( y , f ( x , y ) ) ) = x y 3 x 3 + 2 x 2 y + 2 x y 2 + y 3 0,

f is in F 2 and so Theorem 2.2 is true for f. We also note that for any b, lim x f(x,b)= and so the consequent of Theorem 2.2(ii) holds for any L0 and b and that of Theorem 2.2(iv) for any L0 and b>L.

Finally, we show that R (and hence S) is not necessarily continuous for functions in . Our counterexample uses Proposition 3.2 below, which is a kind of comparison test for functions in . In what follows, we use superscripts (e.g. r n f ) to distinguish between r n , s n , R and S for different functions.

Proposition 3.2 Let f,gF, C>0 and assume that

  1. (i)

    g(x,y) increases in x and decreases in y,

  2. (ii)

    if C<x then g(x,y)f(x,y) and if xC then g(x,y)f(x,y).

Let CL<a, where L is a value of R g . Then there is a b C such that R f (a,b)L for all b b .

Proof Let x x, y y. Then, by (i), g( x , y )g(x,y) and so, by (ii), if C<x then g( x , y )g(x,y)f(x,y). Similarly, if x x, y y and xC then g( x , y )g(x,y)f(x,y).

If CL<a, where L is a value of R g , then R g ( a , b )=L for some a , b such that CL< a a, C b . Then, by the above, for any b such that b b

g ( a , b ) f ( a , b ) , g ( b , g ( a , b ) ) f ( b , f ( a , b ) )

and also, CLL<g( a , b ), Cg( b ,g( a , b )).

Hence, by induction, for all n0, r n g ( a , b ) r n f (a,b) (and s n g ( a , b ) s n f (a,b)). Therefore, R f (a,b) R g (a,b)=L, as claimed. □

Example 3.4 Let fF be defined as

f(x,y)={ x 1 + ( 1 x ) + y if  x 1 , x 1 + y if  x > 1 ,

and put g(x,y)= x 1 + y . We note that f is actually in F 1 , in fact it strictly decreases in y and strictly increases in x.

By Theorem 2.2, the range of R g is [0,). Therefore, by Proposition 3.2, R f has values ≥1, since f(x,y)g(x,y) for x1 and f(x,y)=g(x,y) for x>1. If R f (x,y)<1, then eventually r n f (x,y)<1 and hence R f (x,y)= R f ( x , y ) 1 + ( 1 R f ( x , y ) ) + S f ( x , y ) . Therefore, R f (x,y)=0, i.e. R f has no positive values <1. Since 0 is a value of R f , R f is not continuous. Since R f and S f have the same range, S f is not continuous either. We also note that if x,y1, then R f (x,y)= S f (x,y)=0, since then R f (x,y)<1 and S f (x,y)<1.

References

  1. 1.

    Kent CM: Convergence of solutions in a nonhyperbolic case. Nonlinear Anal. 2001, 47: 4651–4665. 10.1016/S0362-546X(01)00578-8

    MathSciNet  Article  MATH  Google Scholar 

  2. 2.

    Kulenovic MRS, Ladas G: Dynamics of Second Order Rational Difference Equations: With Open Problems and Conjectures. Chapman & Hall/CRC, Boca Raton; 2001.

    Book  MATH  Google Scholar 

  3. 3.

    Janssen AJEM, Tjaden DLA: Solution to problem 86–2. Math. Intell. 1987, 9: 40–43. 10.1007/BF03023954

    Article  Google Scholar 

  4. 4.

    Chan DM, Kent CM, Ortiz-Robinson NL: Convergence results on a second-order rational difference equation with quadratic terms. Adv. Differ. Equ. 2009., 2009: Article ID 985161

    Google Scholar 

  5. 5.

    Kalikow S, Knopf PM, Huang YS, Nyerges G:Convergence properties in the nonhyperbolic case x n + 1 = x n 1 /(1+f( x n )). J. Math. Anal. Appl. 2007, 326: 456–467. 10.1016/j.jmaa.2006.03.018

    MathSciNet  Article  MATH  Google Scholar 

Download references

Acknowledgements

The author would like to thank the referees for their helpful comments and suggestions.

Author information

Affiliations

Authors

Corresponding author

Correspondence to Gabor Nyerges.

Additional information

Competing interests

The author declares that he has no competing interests.

Author’s contributions

The sole author had responsibility for all parts of the manuscript.

Rights and permissions

Open Access This article is distributed under the terms of the Creative Commons Attribution 2.0 International License (https://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Reprints and Permissions

About this article

Cite this article

Nyerges, G. On the convergence of x n =f( x n 2 , x n 1 ) when f(x,y)<x. Adv Differ Equ 2014, 8 (2014). https://doi.org/10.1186/1687-1847-2014-8

Download citation

  • Received:

  • Accepted:

  • Published:

  • DOI: https://doi.org/10.1186/1687-1847-2014-8

Keywords

  • second-order difference equation
  • convergence to zero
  • convergence to prime period two sequences
  • approximating initial conditions for convergence